ESLint: Checking for Syntax and Logic Errors. - Vodnik, Sasha (linkedin.com, 2020)
Reduce bugs and boost efficiency by using ESLint to catch common coding errors. Learn about some of the most essential error-catching rules, as well as how to configure them.